Comparison of the Antimicrobial Properties of Silver Impregnated Vascular Grafts with and without Triclosan. Issue 2 (February 2016) - Berard, X.; Stecken, L.; Pinaquy, J.-B.; Cazanave, C.; Puges, M.; Pereyre, S.; Bordenave, L.; M'Zali, F.
Abstract : Objectives: The aim was to compare the antimicrobial efficacy of the silver impregnated collagen coated polyester vascular graft (IGS) with an identical graft combining silver and triclosan (IGSy). Methods: This was an in vitro study. A non-antimicrobial collagen polyester vascular graft served as control (IG). The IG, IGS, and IGSy grafts were contaminated separately with inoculates of each of the following micro-organisms: Staphylococcus epidermidis (SE), methicillin resistant Staphylococcus aureus (MRSA), and Escherichia coli producing extended spectrum beta-lactamase (ESBL-EC) or Candida albicans (CA). MRSA, ESBL-EC, and CA were obtained from retrieved infected grafts. The in vitro antimicrobial efficacies of the contaminated grafts were evaluated by time to kill assays over a 24 hour period in accordance with CLSI Guideline M26-A. All assays were repeated six times. Bacterial survival numbers were obtained at 1, 4, 8, and 24 hours using a standard plate count procedure. Bactericidal activity was defined as a 3 log10 reduction factor (logRF). To calculate the overall difference in the mean log10  CFU/mL within 24 hours, a one way ANOVA with a Bonferroni correction was calculated separately for each graft. Results: The IG graft showed an increase in the number of viable organisms for the four strains tested. IGSy offered better antimicrobial properties than IGS for both ESBL-EC and MRSA, since only the IGSy graft achieved > 3 logRF and fulfilled the standard criteria for bactericidal activity at 24 hours with 3.78 and 4.08 logRF, respectively. For samples inoculated with SE and CA, both antimicrobial grafts achieved 24 hour bactericidal activity with > 3 logRF. However, for CA the one-way ANOVA analysis demonstrated that the IGSy graft performed differently in terms of speed of antimicrobial action, appearing more active as early as 4 hours following inoculation ( p  = .007). Conclusion: In the in vitro conditions, the Synergy vascular graft combining silver with triclosan demonstrated better short-term antimicrobial activity than the silver graft for all micro-organisms tested.